Interventions to improve school attendance: a systematic review and meta-analysis of evidence from randomised controlled trials - Jean Strelitz; Jessica R Barrett; Nivethigha Elango; Nancy Meligy; Fiona Watson; Juliette Westbrook; Katherine Clarke; Dafydd Huw; Oliver John; Ann John (Journal of Epidemiology and Community Health, 2026)
Background Poor school attendance adversely affects youth behaviour and health trajectories. We reviewed and synthesised the evidence from randomised controlled trials (RCTs) on interventions to improve school attendance. Methods This systematic review and meta-analysis updates the Education Endowment Foundation (EEF) 2022 review on attendance interventions. We synthesised RCT data to inform recommendations. We searched ERIC (via EBSCOhost), PsycINFO, Web of Science and Google Scholar for publications 1 January 2020-16 October 2024 to identify attendance interventions delivered to students, parents/guardians or school staff. We also extracted and analysed RCTs identified in the EEF review. Two reviewers independently extracted data from published articles and assessed risk of bias and certainty of evidence (Grading of Recommendations Assessment, Development and Evaluation, GRADE assessment). We synthesised and meta-analysed data per our protocol (PROSPERO: CRD42024610037). Results We screened 9366 titles and abstracts and included 61 articles (2000-2024): 43 articles published 2020-2024 plus 18 articles from the previous review (2000–2020), reporting 57 trials of 54 interventions. Pooled mean difference and 95% CIs for days of school attended was 0.63 (-0.34 to 1.61), I 2 =64.0%, low certainty, for mentoring interventions and 0.43 (0.10 to 0.76), I 2 =91.9%, moderate certainty, for parental engagement interventions. Other intervention areas including targeted approaches, behavioural programmes and social-emotional interventions had smaller, heterogeneous evidence bases. Risk of bias was moderate-to-low in most trials. Conclusion A large range of interventions exist to address the diverse causes of school absence. Parental engagement demonstrated a small positive effect on attendance, particularly among younger age groups. Most trials were from the USA; implementation and evaluation in other countries will inform effectiveness.